The understanding of race: an analysis of laypeople's contemporary understanding of the notion race - Bodart, Renaat (Social Anthropology, 2023)
This is a thesis about popular perceptions of "race" - the way in which ordinary people in South Africa conceptualise and understand the term. Traditional academic literature on the topic has emphasised the need to differentiate clearly between "popular" and "scientific" conceptions of "race". The scientific conception, it is constantly emphasised, refers to a category based exclusively on physical, genetic, biologically inherited criteria. The popular conception, on the other hand, does not adhere to this strict formulation (Boonzaier,1988:61).